EFFECT OF COW URINE ON LIVER MICROSOMAL ENZYMES IN RATS - R. RASHMI; JAGADEESH; S. SANGANAL; N.B. SHRIDHAR (International Journal of Pharma and Bio Sciences, 2014)
Deoni cow urine was evaluated for its effect on pentobarbitone induced sleeping time in wistar rats. Five groups with ten males and ten females were separately administered with distilled water (control), Chloramphenicol 100 mg/kg i.p, Phenobarbitone sodium 80 mg/kg i.p, cow urine 0.25 ml/kg p.o, cow urine 0.5 ml/kg p.o for seven days. After 30 min of last dose treatment pentobarbitone sodium 35 mg/kg i.p was administered to all groups except group III and sleeping time was recorded. After 24 h of last dose treatment pentobarbitone sodium 35 mg/kg i.p was administered to group III and sleeping time was recorded. The pentobarbitone sleeping time significantly increased in treated (Group II, IV and V) compared to their respective control group. This can be attributed to the inhibitory effect of cow urine on liver microsomal enzymes. Length of sleeping time after pentobarbitone administration is inversely related to the rate of drug metabolism.